Project portfolio risk management: a structured literature review with future directions for research - Mican, Camilo (2020)
Project Portfolio Risk Management (PPRM) has been identified as a relevant area regarding project portfolio success. This paper reports on a structured literature review of PPRM. A structured search and selection process was carried out and conventional content analysis was conducted in the literature analysis of 62 papers published in international journals. PPRM has its theoretical and practical bases in the modem theory of portfolios, decision theory and risk management (RM). The content analysis reveals four main recurrent topics in PPRM: (1) The influence of RM on project portfolio success, based on project portfolio impact level, moderators or contingency factors between RM and project portfolio success, and PPRM dimensions; (2) risk and project interdependencies, highlighting resources, technology, outcome, value, and accomplishment project interdependencies; (3) project portfolio risk (PPR) identification, where four main risk source categories are identified; and (4) PPR assessment, composed of risk measures and the main methods used for risk assessment. Therefore, this study provides an overview of PPRM as a research field, while it also promotes four future research directions: (1) PPRM as part of organizational RM (2) RM, success dimensions and strategic impact; (3) mechanisms for PPR assessment, and (4) PPRM as a complex and dynamic system.